2021
DOI: 10.1186/s12879-021-05977-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic expression of cholesterol regulating genes favour increased circulating low-density lipoprotein in HIV infected patients with gallstone disease: a preliminary study

Abstract: Background HIV endemic populations are displaying higher incidence of metabolic disorders. HIV and the standard treatment are both associated with altered lipid and cholesterol metabolism, however gallstone disease (a cholesterol related disorder) in Sub-Saharan African populations is rarely investigated. Methods This study sought to evaluate hepatic expression of key genes in cholesterol metabolism (LDLr, HMGCR, ABCA1) and transcriptional regulato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“… [ 37 ] HIV LDLR levels in mononuclear cells of the liver and blood are down-regulated in HIV-positive patients with lipodystrophy, independent of PI-ART, compared to HIV-negative controls and positive patients without lipodystrophy. [ 38 , 39 ] Dengue virus For DENV to proliferate and be introduced, cholesterol is essential. Furthermore, it was shown that soon after infection, there was an increase in lipid raft formation and total cholesterol levels.…”
Section: Cholesterol and Ldl In Viral Infectionmentioning
confidence: 99%
“… [ 37 ] HIV LDLR levels in mononuclear cells of the liver and blood are down-regulated in HIV-positive patients with lipodystrophy, independent of PI-ART, compared to HIV-negative controls and positive patients without lipodystrophy. [ 38 , 39 ] Dengue virus For DENV to proliferate and be introduced, cholesterol is essential. Furthermore, it was shown that soon after infection, there was an increase in lipid raft formation and total cholesterol levels.…”
Section: Cholesterol and Ldl In Viral Infectionmentioning
confidence: 99%
“…While BMI has not directly been linked to hepatic nuclear factors, a high fat diet has been shown to upregulate HNFs. Our previous paper on cholesterol signaling showed that despite having a lower BMI, this group displayed mRNA profiles similar to those expected in people with higher BMIs [ 63 ].…”
Section: Discussionmentioning
confidence: 74%
“…The HIV-positive group had higher total cholesterol with significantly elevated LDL-C levels than uninfected controls, while the scavenging LDLR for LDL-C was significantly decreased in the HIV group. The transcriptional regulator of LDLR, SREBP2, was decreased in HIV-positive patients; besides this, the regulatory miR-148a-3p was reduced with a concomitant increase in target ABCA1, regulating cholesterol efflux [ 112 ].…”
Section: Hivmentioning
confidence: 99%
“…ROS production is mediated by the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) family complex as NOX1, NOX2, NOX4, and NOX5 [ 5 , 124 ]. NOX members are found in muscle tissue and represent the primary sources of ROS; its activity has been investigated in conditions such as hypertension, hypercholesterolemia, and endothelial dysfunction [ 110 , 111 , 112 , 125 , 126 , 127 ]. Another enzyme that generates ROS is xanthine oxidoreductase, principally found in the liver and gut, although distributed in smaller proportions in the lungs, kidneys, heart, and brain plasma.…”
Section: Hivmentioning
confidence: 99%